Computational Intelligence - Sadiku, Matthew N. O.; Foreman, Justin; Musa, Sarhan M. (European Scientific Journal, ESJ, 2018)
Computational intelligence (CI) refers to recreating human-like intelligence in a computing machine. It consists of a set of computing systems with the ability to learn and deal with new situations such that the systems are perceived to have some attributes of intelligence. It is efficient in solving realworld problems which require reasoning and decision-making. It produces more robust, simpler, and tractable solutions than the traditional techniques. This paper provides a brief introduction to computational intelligence.